Computational Engineering - Debney Peter (Institution of Structural Engineers (ISTRUCTE), 2020)
We are on the verge of a new generation of technology and innovation. Finite Element Analysis is being linked parametrically with CAD; artificial intelligence and machine learning are being applied to everyday engineering tasks. What does today's graduate (and those with more experience too) need to know about these 'engineering assistants' in order to harness their full potential? Author takes the reader on a practical, theoretical, and philosophical journey; balancing a complex subject with a fresh, engaging, and often humorous style. Forewords from Chris Wise, Tristram Carfrae, and Jon Leach precede chapters that discuss: Design (including parametric design), Modelling (and its problems), Analysis (basics and methods/linear, nonlinear, and dynamic), Optimisation, AI and machine learning, The future of engineering software. An extensive reference list supports the text.